Legalitas Perampasan Aset Illicit Enrichment: Analisis Kekosongan Hukum Dalam Undang – Undang Tipikor - Alvin Amadeus Jaya Mahendra; M Abd. Rohim; Rismalia Putri Anggraini (Universitas Sains dan Teknologi Komputer, 2026)
Corruption is recognized as an extraordinary crime that undermines national foundations and hinders development. A major challenge in its eradication is the recovery of assets suspected to be derived from corruption but difficult to prove, known as illicit enrichment. This research aims to analyze the legality of illicit enrichment asset forfeiture and identify legal gaps within the Indonesian Anti-Corruption Law (UU Tipikor). The research employs a normative legal method with statutory and comparative approaches. The findings reveal a fundamental legal vacuum in UU Tipikor, as there are no explicit regulations on illicit enrichment, despite Indonesia's ratification of UNCAC. The current legal system remains heavily dependent on proving the predicate crime, which complicates law enforcement efforts to seize unexplained wealth. This study contributes to the development of criminal law, both theoretically and practically, by providing recommendations for the formulation of the Asset Forfeiture Bill (RUU Perampasan Aset). In conclusion, the enactment of the Asset Forfeiture Bill, which integrates concepts of illicit enrichment and Non-Conviction Based Asset Forfeiture (NCBAF), is a crucial step toward strengthening the legality of state asset recovery while maintaining human rights protections.